Pengembangan Ekonomi Kerakyatan Berbasis Teknologi di Lingkungan RW 04 Palmerah-Jakarta Barat - Nur Chairat, Arief Suardi; Wahyunungsih, Utami; Rasyidi, Lili; Desiawan, Victor Assani; Kusumastuti, Dyah Pratiwi; Caswito, Ade (Universitas Pahlawan Tuanku Tambusai, 2024)
In 2018, RW 04 Palmerah, located in the administrative region of Palmerah, West Jakarta, was designated as one of the slum neighborhoods under Jakarta Governor Regulation No. 90. A critical aspect of this regulation addressed the issues of plastic waste and community economic empowerment. Within the context of Community-Based Economic Development through Technology in RW 04 Palmerah, community engagement initiatives aimed to address plastic waste management and enhance economic well-being through technological interventions. Employing a participatory approach, the implementation over two months not only cultivated a clean culture but also effectively processed and utilized plastic waste within the community. Despite modest and fluctuating returns, the initiative significantly contributed to the sustainable model of community-based economic development through technology in the local area, serving as a guiding framework for similar endeavors in other regions.